Supplementation with essential amino acids in the early stage of carbohydrate reintroduction after a very-low energy ketogenic therapy (VLEKT) improves body cell mass, muscle strength and inflammation - Giuseppe Annunziata; Ludovica Verde; Vincenzo D’Orsi; Massimiliano Caprio; Stefania Gorini; Silvia Savastano; Annamaria Colao; Giovanna Muscogiuri; Luigi Barrea (Journal of Translational Medicine)
Abstract Background Although little is yet known about the long-term maintenance of very low-energy ketogenic therapy (VLEKT) effects on body composition, muscle strength and inflammation, it is plausible to assume that changes may occur, particularly during the steps following the ketogenic step, due to the loss of the protective effects of ketones and the concomitant reintroduction of carbohydrates. For this reason, the present study aimed to evaluate the effects of supplementation with 8 g per day of essential amino acids (EAAs) on these parameters. Methods A total of 68 women of reproductive age and with grade I obesity who had completed 45 days of the ketogenic phase with VLEKT (KeNuT protocol) and 40 days of non-ketogenic phase of KeNuT protocol with VLEKT (phase 3, fruit reintroduction) were included in the study. Half of them (n = 34) followed this first step of the re-educational phase of KeNuT protocol with VLEKT with supplementation with EAAs (Aminotrofic®: 4 g twice daily). Anthropometric parameters, body composition via bioelectrical impedance analysis and high-sensitivity C-reactive protein (hs-CRP) levels were assessed at baseline, pre- and post both dietary interventions. Results At the end of 45 days of ketogenic phase with VLEKT (before fruit reintroduction and EAA supplementation), the two groups did not differ in any of the parameters assessed. At the end of the fruit reintroduction phase, the supplemented group showed greater magnitudes of reduction in weight, waist circumference, fat mass (FM) and hs-CRP (p < 0.001 for all) and of increase in muscle strength (p < 0.001), phase angle (p < 0.001), body cell mass (BCM) (p = 0.001), and muscle mass (%) (p < 0.001). Conclusion These results underline the usefulness of supplementation with EAAs during the first transitional phase post VLEKT to improve body composition (specifically reduction in FM and increase in BCM), muscle strength, and inflammatory status.